Rancang Bangun Sistem Informasi Manajemen Kegiatan Ekstrakurikuler di SMA Negeri 9 Padang - Wahyuni, Meisya Alifia; Dewi, Ika Parma; Irfan, Dedy; Marta, Rizkayeni (Lembaga Yasin AlSys, 2025)
Extracurricular activities play a crucial role in developing students' character and potential; however, their management, which remains manual in many schools, including SMA Negeri 9 Padang, results in inefficiency and susceptibility to errors. This study aims to design and develop a web-based extracurricular activity management information system to enhance management effectiveness. The method used is Rapid Application Development (RAD), consisting of the stages of requirement planning, system design, and implementation. Data were collected through observation, interviews, and document studies, while system performance testing was conducted using GTmetrix. The system was developed using the CodeIgniter framework and MySQL database. Testing results showed excellent system performance with a GTmetrix Grade A, high page load speed (Performance 98%), and efficient code structure (Structure 92%). All Web Vitals metrics were within the